Comparative Study About Youth Body Height by Age Group and BMI at Medical Faculty of UMM - Anung Putri Ilahika; Wiby Fahmi Wijaya (Saintika Medika, 2020)
Growth and development is a continuous process in the process of reaching adulthood, including the teenage stage. The problem that is often faced is physical change. Adolescent physical changes that appear are the increase in height and weight which affects the Body Mass Index (BMI). Height is one of the important things in adolescent growth and development. which is affected by genetic and environmental factors. The peak of growth in adolescents is different between boys and girls, so the pattern of height and BMI are also different. The purpose of this study was to determine differences in adolescent height based on age groups and BMI in Medical Faculty of UMM. This research is a comparative study by taking a sample of 100 medical students of UMM who have an age range of 17-20 years. The data to be taken is height measured using a MIC scale health scale ratio ratio. The measurement results have a numerical scale with units of centimeters (cm). Body mass index (BMI) is an index obtained from the division of body weight with height2. The measurement results are stated in kg / m2. All data obtained will be analyzed using the ANOVA comparative test. ANOVA test results generated p value in the two groups of students> 0.05 which concluded that the mean height of the student body based on age and BMI was not significantly different (not significant) statistically for both men and women. The conclusion from this study there were no differences in adolescent height based on age groups and BMI among medical students of UMM.